Structure Design of Wheel Sliding Device for 1 435/1 520 mm Gauge Changeable Rail - Chao LIU; Dianmai ZHOU; Zhihui HUANG; Zhaojin LIU; Ruichen KONG (机车电传动)
In order to realize 1 435/1 520 mm non-stop gauge changeable, it is necessary to design wheel sliding device with different structure of traditional wheelset axle box. This paper mainly introduced the special matching mode, torque transmission mode and sliding mode of wheel slip device. The analysis showed that this structure design can realize the rail transfer of 1 435/1 520 mm train under the condition that the inner distance of wheelset can be changed without stopping.